La producción empresarial y la tasa de ganancia. Perú: 2001 – 2020 - Chumacero, José Antonio (2023)
The objective of this article is to determine to what extent the business profit rate impacts business production in Peru during the period 2001-2020. For the study, the agricultural, industrial and mining sectors were analyzed, choosing as a sample the companies registered in the Lima Stock Exchange of the respective sectors. Being the panel type database, the econometric technique is used for grouped data. It is concluded that before a 1% change in the profit rate, business production grows by 1677.07 (2000 soles).